Homicide Waiting to Happen: Sacrifice and Corporate Manslaughter Law in the UK - Hebert, Jasmine (Université d'Ottawa / University of Ottawa, 2018)
The original purpose or motive of the sacrifice, rooted in ceremonious or religious acts, was as a gift to a centralized power that ensured a common good or prosperity. In modern capitalist society, sacrifice is about “a willingness to sacrifice short-term gains for long-term gains” (Keenan 2005: 11) of freedom and fortune. What is concealed in this propaganda is that true freedom and prosperity is mostly restricted to a few exceedingly privileged and powerful individuals – and every year, these ‘short-term’ sacrifices include the millions of lives of the disciplined and altruistic workers that the system supposedly admires. Within this context, in recent years a growing recognition of the social and economic harms that corporations are capable of causing, specifically against workers and members of the public, led to the development of laws in several countries aimed at corporate manslaughter and corporate criminal liability. However, despite these legal advancements, the law continues to fail at protecting the victims of corporate harm and wrongdoing, and to adequately hold corporations and their actors accountable for their crimes. This research asks the following question: what role does corporate manslaughter law play in the reproduction of sacrifice and, in the process, violence and capitalist hegemony? This is done by interrogating the introduction and enforcement of corporate manslaughter law in the United Kingdom and the struggle for corporate criminal accountability from the socio-historical perspective of advanced neoliberal capitalism. Employing a theoretical lens that draws together literatures on sacrifice, law, and violence, this research shows that the law (re)produces particular understandings of sacrifice and violence that benefit the powerful, therein normalizing death and dying at work as the natural and largely unavoidable costs of modern employment relations. The research concludes that, to better address the systemic violence faced by workers, we must consider a restructuring of the legal enterprise and the ‘common sense’ understandings of sacrifice, violence, and harm that accompany it.
Keywords: Corporate Crime; Corporate Violence; Sacrifice; Occupational Health and Safety